1991
DOI: 10.1271/bbb1961.55.1027
|View full text |Cite
|
Sign up to set email alerts
|

Ovomucin-food protein conjugates prepared through the transglutaminase reaction.

Abstract: Ovomucin-protein conjugates were prepared to develop a new kind of functional glycoprotein-protein conjugates. Soluble reduced ovomucin was self-associated by transglutaminase and the reactant had better foaming and emulsifying properties than untreated ovomucin. The conjugation of ovomucin with casein or soy protein was also attempted by transglutaminase.Ovomucin-llS globulin and ovomucin-asl-casein conjugates were formed by cross-linking between ovomucinand IIS globulin or asl-casein. Themolecular weight of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…Similar results were reported for an ovalbumin-dextran mixture , a Pronase-treated gluten-dextran mixture (Kato et al, 1991b), and a lysozyme-dextran conjugate (Nakamura et al, 1990). The result indicated that TGase may have catalyzed the transfer reaction between an amide group in a protein-bound glutamine and an -amino group in a protein-bound lysine side chain, resulting in crosslinks between the protein molecules (Nonaka et al, 1989;Kato et al, 1991a;Sakamoto et al, 1994Sakamoto et al, , 1995Sergo et al, 1995). The result indicated that TGase may have catalyzed the transfer reaction between an amide group in a protein-bound glutamine and an -amino group in a protein-bound lysine side chain, resulting in crosslinks between the protein molecules (Nonaka et al, 1989;Kato et al, 1991a;Sakamoto et al, 1994Sakamoto et al, , 1995Sergo et al, 1995).…”
Section: Effect Of Various Modifications On the Molecular Mass Of Soysupporting
confidence: 76%
See 1 more Smart Citation
“…Similar results were reported for an ovalbumin-dextran mixture , a Pronase-treated gluten-dextran mixture (Kato et al, 1991b), and a lysozyme-dextran conjugate (Nakamura et al, 1990). The result indicated that TGase may have catalyzed the transfer reaction between an amide group in a protein-bound glutamine and an -amino group in a protein-bound lysine side chain, resulting in crosslinks between the protein molecules (Nonaka et al, 1989;Kato et al, 1991a;Sakamoto et al, 1994Sakamoto et al, , 1995Sergo et al, 1995). The result indicated that TGase may have catalyzed the transfer reaction between an amide group in a protein-bound glutamine and an -amino group in a protein-bound lysine side chain, resulting in crosslinks between the protein molecules (Nonaka et al, 1989;Kato et al, 1991a;Sakamoto et al, 1994Sakamoto et al, , 1995Sergo et al, 1995).…”
Section: Effect Of Various Modifications On the Molecular Mass Of Soysupporting
confidence: 76%
“…The enzyme was inactivated by N-ethylmaleimide (0.1 mL, 0.1%) (Kato et al, 1991a). APP (10 mg/ mL) in 0.1 M phosphate buffer (pH 7) was reacted with TGase (0.2 mg/mL).…”
Section: Preparation Of Acid-precipitated Soy Protein (App)mentioning
confidence: 99%
“…More than two different proteins can be covalently conjugated by MTGase to produce new proteins with novel functionalities, as with the guinea pig transglutaminase. For instance, conjugation of caseins or soybean globulins with ovomucin, one of the egg white glycoproteins, improved emulsifying activity (44). Also casein/gelatin conjugation yielded novel proteins highly soluble in acidic pH regions (45).…”
Section: Microbial Transglutaminase Derived From a Variant Of Streptomentioning
confidence: 99%
“…Many attempts to improve textural properties of foods through formation of E-(y-Glu)Lys crosslinks by the catalytic action of transglutaminases (TGase) have been reported (Ikura et al, 1980a(Ikura et al, , 1980bMotoki and Nio, 1983;Kurth and Rogers, 1984;Kato et al, 1991). These enzymes have been found in many cells, organisms and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The crosslink results from interaction between the y-carboxyamide group of peptide-bound glutamine residues and E-amino group of peptide-bound lysine residues (Pisano et al, 1968;Williams-Ashaman et al, 1972;Folk and Chung, 1973;Folk and Finlayson, 1977;Birckbichler et al, 1981). Intermolecular crosslinks in several proteins were induced using guinea pig liver TGase and bovine plasma TGase (Ikura et al, 1980a(Ikura et al, , 1980bMotoki and Nio, 1983;Kurth and Rogers, 1984;Bercovici et al, 1987;Kato et al, 1991). Motoki and Nio (1983) and Nio et al (1985Nio et al ( , 1986aNio et al ( , 1986b) purified the TGase from guinea pig livers and reported that many other food proteins, as well as soybean protein and bovine casein, were substrates and formed gels on incubation with the enzyme.…”
Section: Introductionmentioning
confidence: 99%